Relação entre variáveis climatológicas e morbimortalidade por doenças respiratórias em crianças e idosos no município de Aracaju-SE - Barreto, Shirley Azevedo (2022)
Climate variations have generated increasing concern about potential health effects of humanity, especially those related to diseases that can cause an increase in morbidity and mortality in different regions of the world, especially in developing countries. In this sense, this research aims to analyze the influence of the weather variables and the morbidity and mortality of children and the elderly, by respiratory diseases in the municipality of Aracaju. As a universe of research, the geographical area of Aracaju was chosen, located in the northeast region of Brazil and, due to the rapid and large increase in urban development, has been causing environmental degradation, greatly influencing the health of the resident population in the municipality in the above municipality. An analysis of the relationship between the weather variables was performed: temperature, relative humidity, rainfall, wind velocity, and occurrences of diseases and deaths because of respiratory diseases in children groups (0-4 years) and elderly (over 60), as well as gender. The method of approach used was the deductive hypothetical, quantitative, regarding the method of procedure, statistical techniques were used in order to generate results and knowledge through practical execution. Data collection was performed through the search for information at the Digital Database of the National Institute of Meteorology (Inmet) and the Brazilian Institute of Geography and Statistics (IBGE), to direct the arrangement of climatic and population factors, against the study Descriptive epidemiological, conducted from data information on morbidity and mortality recorded in the Database of the Municipal Health Secretariat of Aracaju and Datasus. The sample is composed of mortality cases in the municipality from 2000 to 2020, as well as the cases of morbidity from 2008 to 2020. Statistical results pointed out that the weather variables, in the measurements obtained for the city of Aracaju, Studied periods, they were not suitable to describe the behavior of morbidity and mortalities that occurred in the elderly in female and male genres and the group of children, in analysis performed through the multivariate technique of regression and canonical correlation analysis. In this sense, we understand, therefore, that weather variations in Aracaju did not have statistical significance in respiratory diseases, but correlation analysis showed significant results in cases of pneumonia, as there is also an expressive relationship of morbidity and mortality data with climatic periods by respiratory diseases in children and the elderly. Finally, we conclude that weather variables have greater influence on morbidity in children and elderly than on mortality.